Jacob Berzelius - Soderbaum, H. G. (Henrik Gustaf) (Norstedts förlag, 1901)
Title page and frontispiece have been digitized from this work on Swedish chemist Baron Jöns Jakob Berzelius (1779-1848). Considered one of the founders of modern chemistry and known as the "Father of Swedish Chemistry," he is best known for his determination of atomic weights, chemical notation, and the isolation and discovery of silicon, selenium, thorium and cerium.
Keywords: Kungl. Svenska vetenskapsakademien; Norstedts förlag; Berzelius, Jöns Jakob, friherre, 1779-1848; Soderbaum, H. G. (Henrik Gustaf), 1862-